2017
DOI: 10.1002/jcp.25512
|View full text |Cite
|
Sign up to set email alerts
|

Dedicator of Cytokinesis 2 in Cell Signaling Regulation and Disease Development

Abstract: Dedicator of cytokinesis 2 (DOCK2) is a CDM family protein containing DOCK homology region (DHR)-1 and DHR-2, Src-homology 3 (SH3) domain, and C-terminal polybasic amino acid cluster. The CDM family consists of 11 mammalian members and is classified into four subfamilies, the DOCK-A, -B, -C, and -D. DOCK2 is a member of DOCK-A subfamily and an atypical guanine exchange factor regulating the loading of GTP to activate Rac. It is primarily found in peripheral blood, spleen, and thymus and mainly expressed in lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 143 publications
(236 reference statements)
1
17
0
Order By: Relevance
“…Among DOCK proteins, DOCK2 plays multiple roles in regulating immune responses 32 . It is a haematopoietic cell protein which functions downstream of chemokine receptors to control actin reorganization, thus, regulating lymphocyte activation, migration, and morphology 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among DOCK proteins, DOCK2 plays multiple roles in regulating immune responses 32 . It is a haematopoietic cell protein which functions downstream of chemokine receptors to control actin reorganization, thus, regulating lymphocyte activation, migration, and morphology 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Among DOCK proteins, DOCK2 plays multiple roles in regulating immune responses 32 . It is a haematopoietic cell protein which functions downstream of chemokine receptors to control actin reorganization, thus, regulating lymphocyte activation, migration, and morphology 32 , 33 . In T cells DOCK2 acts downstream of the T cell receptor, and recently DOCK2 was implicated in mediating signalling from the FLT3 protein tyrosine kinase and identified as a leukaemia drug target 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The increased inflammation in adipose tissue and low-grade system inflammation appear to be important (28). DOCK2 regulates lymphocyte activation and various immunological functions indicating a vital role in regulating inflammation (16). Indeed, the attenuation of diet-induced obesity Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dedicator of cytokinesis 2 (DOCK2) is an atypical guanine nucleotide exchange factor (GEF) for the Rho-small guanine triphosphatase mainly expressed in hematopoietic cells that regulates lymphocyte activation and migration (15). DOCK2 also controls various immunological functions including helper T cell differentiation, neutrophil chemotaxis, and type I interferon induction (16). Recently, we found that DOCK2 modulates SMC phenotype by inhibiting myocardin-mediated SMC gene transcription (17).…”
mentioning
confidence: 99%
“…Herein, we observed that the highest number of ligand peptides reported were for SH3, WW and PDZ domains. Proteins containing these domains were known to play crucial roles in critical diseases like cancer and neurodegenerative disorders [ 18 23 ], and hence, peptides binding to these three domains were extensively studied. Although prediction servers have been previously developed for SH3, WW and PDZ binding peptides, we selected SH3, WW and PDZ domains for developing better prediction methods for domain-specific peptide interactions.…”
Section: Introductionmentioning
confidence: 99%